High-quality total RNA extraction from early-stage lamprey embryos - Sugahara, Fumiaki (BioTechniques, 2023)
High-purity total RNA extraction from animal embryos is essential for transcriptome analyses. lampreys, together with hagfish, are the only extant jawless vertebrates or cyclostomes and are thus key organisms for EvoDevo studies. However, extracting uncontaminated RNA from early-stage embryos remains challenging. RNA does not bind to the silica membrane in filter-based extractions, significantly reducing yields; and ethanol/isopropanol precipitation methods lead to contaminants, bringing down the optical density (OD) 260/280 ratio. The RNA extraction protocol was modified using precentrifugation and adding salts before isopropanol precipitation. This modification significantly increased RNA yield, removed contaminants and improved RNA integrity. Egg membrane sources were suspected to cause RNA purification problems because low-quality extraction does not occur in posthatching embryos